ANALISIS PELANGGARAN ETIKA PROFESI AKUNTANSI STUDI KASUS PT PERTAMINA (PERSERO) - Gultom, Megawati; Saridawati,S.E.,M.M; Asril Azzurialsyah; Nevia Blessri Atalya Saragih (Cahaya Ilmu Bangsa, 2025)
. In the modern business world, accounting professional ethics are an important foundation in maintaining public trust and the integrity of financial reports. However, in reality, there are still many cases of violations of professional ethics that occur, one of which is in a state-owned company such as PT Pertamina (Persero). This article aims to analyze violations of accounting professional ethics at PT Pertamina by examining the background of the case, the form of violation that occurred, the causal factors, and its legal implications. This study uses a literature study method and descriptive qualitative analysis by referring to secondary data from official reports, reliable news, and scientific literature. The results of the study indicate that ethical violations at PT Pertamina not only have an impact on the company's financial losses, but also reduce the company's reputation in the eyes of the public. Therefore, it is important for every accountant to uphold the principles of professional ethics such as integrity, objectivity, professional competence, confidentiality, and professional behavior. This article is expected to be a learning material and reflection for accounting practitioners to be more careful in carrying out their professional duties.